Ultra lightweight Mg foam from recycled shavings - Oldani, Carlos Rodolfo (2018)
Hundreds of people worldwide die or are severely maimed in collisions during traffic accidents, due to the energy transmitted to the passengers on impact. A dissipation of said energy is necessary to minimize it's effects, which can be achieved through absorbers. In recent years, metallic foams have started to be considered as energy absorbers. Metallic foams are relatively unknown structural materials, but with huge potential for applications where low weight but high rigidity are of primary interest. The use of ultralight magnesium (Mg) or magnesium alloy foams has two main advantages: less weight (more vehicle efficiency and less pollution) and impact energy absorption (less harm to passengers on board the vehicle). The machining of gearboxes made out of AZ91D magnesium alloy, generates large amounts of oilcontaminated metallic shavings. In this work, powder metallurgy is used as a recycling method of the AZ91 alloy. There were studied the conditions needed for obtaining metallic foam from recycled shavings of AZ91 and spacer (ammonium bicarbonate). The final product was characterized physically by determination of the foam's density. Also, compression tests were done to obtain values of absorbed energy, and specific absorbed energy, which characterize a metallic foam. Different metallography methods were used to characterize the structure of the sintered material. Different porosities were tested (50 and 70%). The foam's absorbed energy by unit mass [J/g] of the 50 % of porosity foam was over double compared to that of the magnesium sintered without spacer.